Epidemiologic and health care surveillance in workers exposed and past-exposed to vinyl chloride monomer in Ravenna/Italy - Mancini, Gianpiero; Rambaldi, Rossella; Olanda, Sandra; Fava, Maria Edoarda; Angelini, Raffaella (La Medicina del Lavoro, 2018)
Italian laws indicate that workers exposed to occupational carcinogens must undergo a program of health surveillance both during and after their working lifetime, but they do not specify who exactly should perform that program once the worker has stopped working at the plant. In Ravenna (Emilia-Romagna, Italy) there is a well-defined population of workers who, having been employed in a big chemical plant producing vinyl chloride monomer (VCM) as well as vinyl chloride polymer, were exposed to this substance for years. As well-known, VCM is a powerful carcinogen for the liver, causing hepatic angiosarcoma (EAS) and hepatocellular carcinoma (HCC). In the early 2000s, the Department of Public Health of Local Health Unit of Ravenna (now Romagna), under the approval of the Regional Health System, decided to start up a health control program addressed to the population of workers past-exposed to VCM. About 550 of them adhered voluntarily to the program, still active by now, and were submitted to a medical examination, annual abdominal ultrasound and other specific laboratory tests to detect liver diseases. Although the effectiveness of a program of medical health surveillance for workers past-exposed to VCM is not definitely confirmed, our experience has proved to be an inexpensive way of taking care of these populations with a defined medical surveillance and counseling program.